Passive Dietary Monitoring - the use of wearable cameras and AI to quantify dietary intake - Lo, Benny (2022)
Benny Lo POLICY SEMINAR Nudging for Good: AI driven diagnostics and behavior change to improve diets and nutrition JUL 28, 2022 - 12:00 TO 2:00PM EDT